Histoenzymic determination of activity of alkaline phosphatase and succinate dehydrogenase in the renal tissue of rats at NADP administration on the background of 31-days experimental diabetes mellitus - Grytsiuk, M. I. (Journal of Education, Health and Sport, 2017)
The article presents data on the activity of some enzymes of rats’ renal tissue in experimental diabetes mellitus in the early period of its formation. It was found that at 31 days of the experiment, the administration of NADP significantly increases the activity of ALP by more than twice, thereby improving the functioning of the proximal tubules in particular, and restores almost normal SDH activity, which allows us to assume that the positive metabolic effects of NADP are not only at the level of general metabolism, but also specifically at the organ level - the kidneys.